Solid phase synthesis of a thrombin binding aptamer on macroporous silica for label free optical quantification of thrombin. Issue 90 (13th September 2016) - Terracciano, Monica; De Stefano, Luca; Borbone, Nicola; Politi, Jane; Oliviero, Giorgia; Nici, Fabrizia; Casalino, Maurizio; Piccialli, Gennaro; Dardano, Principia; Varra, Michela; Rea, Ilaria
Abstract : Human α-thrombin (TB) is a serine protease with a crucial role in coagulation and hemostasis. Abstract : Human α-thrombin (TB) is a serine protease with a crucial role in coagulation and hemostasis. The monitoring of the TB level in blood serum could be of great importance in order to prevent serious damage to human health. In this work, an aptasensor is realized by in situ synthesis of a 17-mer Thrombin Binding Aptamer analogue (TBATT ) on silanized macroporous silica (PSi). The interaction between TBATT and TB at different concentrations is monitored by a label-free optical method, spectroscopic reflectometry, and quantified by fast Fourier transform (FFT) analysis. A TBATT -TB affinity constant of 14 ± 8 nM and limit of detection of 1.5 ± 0.3 nM are demonstrated. The selectivity and reversibility of the aptasensor are also proved.